K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 11 2022

`(2x-6)^3=8`

`(2x-6)^3=2^3`

`2x-6=2`

`2x =2+6=8`

`x=8/2=4`

3 tháng 11 2022

(2x-6)^3=8

(2x-6)^3=2^3

2x-6=2

2x=8

x=4.

Vâỵ x= 4.

16 tháng 12 2018

2x - 8 = -6

=> 2x = -6 + 8 = 2

=> x = 2 : 2 = 1

16 tháng 12 2018

2x-8=6

2x    =6+8

2x    =14

x      =14:2

x      =7

Vậy x=7

23 tháng 4 2019

Chỉ có một \(\frac{3}{8}\)thôi nha

11 tháng 5 2023

dễ

11 tháng 5 2023

2,7 kg nhé

 

2 tháng 11 2023

a, 89 - (73 - \(x\)) = 20

           73 - \(x\)   = 89 - 20

          73 - \(x\)    = 69

                 \(x\)    = 73 - 69

                  \(x\)  = 4

2 tháng 11 2023

b, 7\(x\) - 2\(x\) = 617:615 + 44:11

    5\(x\)        = 62 + 4

    5\(x\)        = 36 + 4

    5\(x\)        = 40

      \(x\)        = 40: 5

       \(x\)       = 8

 

18 tháng 6 2021

2 + 4 + 6 + 8 + ... + 2x = 1056

=> ( 2x + 2 ) . [( 2x - 2 ) : 2 + 1 ] : 2 = 1056

=> 2(x + 1 ) . ( x - 1 + 1 ) = 1056 . 2 = 2112

=> 2( x + 1 ) . x = 2112

=> (x + 1 ) . x = 1056

=> ( x + 1 ) . x = 33 . 32

=. x = 32

Vậy x = 32

10 tháng 10 2016

2+4+6+8+...+2x=210

+) Ta có : 2.1+2.2+2.3+2.4+...+2x=210

=>2.(1+2+3+...x) =210

1+2+3+...+x= 210:2

1+2+3+...+x= 105

(x+1).x:2=105 =>(x+1).x=210 =>15.14=210          

+)  Vậy x=14

5 tháng 5 2019

\(\frac{6}{11}\cdot\frac{3}{14}+\frac{-5}{16}+\frac{3}{14}\cdot\frac{5}{11}+\frac{-3}{16}\)

\(=\frac{6}{11}\cdot\frac{3}{14}+\frac{3}{14}\cdot\frac{5}{11}+\frac{-5}{16}+\frac{-3}{16}\)

\(=\frac{3}{14}\cdot\left(\frac{6}{11}+\frac{5}{11}\right)+\left(\frac{-5}{16}+\frac{-3}{16}\right)\)

\(=\frac{3}{14}\cdot\frac{6+5}{11}+\frac{-5+\left(-3\right)}{16}\)

\(=\frac{3}{14}\cdot\frac{11}{11}+\frac{-8}{16}\)

\(=\frac{3}{14}\cdot1+\frac{-1}{2}\)

\(=\frac{3}{14}+\frac{-1}{2}\)

\(=\frac{3}{14}+\frac{-7}{14}\)

\(=\frac{3+\left(-7\right)}{14}\)\(=\frac{-4}{14}=\frac{-2}{7}\)

5 tháng 5 2019

\(\frac{-5}{6}+\left(7x-\frac{1}{2}\right)\cdot\frac{2}{9}=-1\frac{1}{3}\)

       \(\frac{-5}{6}+\frac{14}{9}\cdot x-\frac{1}{9}=-\frac{4}{3}\)

                       \(\frac{14}{9}\cdot x-\frac{1}{9}=-\frac{4}{3}+\frac{5}{6}\)

                       \(\frac{14}{9}\cdot x-\frac{1}{9}=-\frac{1}{2}\)

                                   \(\frac{14}{9}\cdot x=-\frac{1}{2}+\frac{1}{9}\)

                                   \(\frac{14}{9}\cdot x=-\frac{7}{18}\)

                                              \(x=-\frac{7}{18}:\frac{14}{9}\)

                                              \(x=-\frac{1}{4}\)